The Enforcement Of Equal Employment Opportunity: Indonesian And Taiwanese Perspective - Falah Al Ghozali; Shu-Mei Tang (Universitas Duta Bangsa Surakarta, 2022)
ABSTRACT: Accommodating diversity and promoting equality in the workplace represents a substantial challenge both now and in the future. Two Asian countries: Indonesia and Taiwan have been restructuring the Equal Employment Opportunity (EEO) due to employment discrimination issues. The laws on the EEO can be found in both Indonesia and Taiwan. The right to equal employment opportunity is acknowledged. However, its enforcement remains a formidable challenge. The EEO enforcement is expected to eliminate discrimination and achieve equality at work, employees within the organization have the right to be treated justly in all matters of employment. In regards to the enforcement, Indonesia and Taiwan have their own EEO enforcement agencies. These agencies are crucial and are responsible in ensuring the EEO laws in the countries. These agencies, however, are not an independent state agency. By having normative legal research, the author analyzes the facts on the issue of discrimination in employment in Indonesia and Taiwan. Moreover, the study aims to describe how both Indonesia and Taiwan guarantee the EEO for their citizens. In addition, the study shows the works of those agencies and how they function in order to reduce employment discrimination rate in their respective countries.